2017
DOI: 10.5535/arm.2017.41.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenge of Diffusion Tensor Imaging in a Patient With Hemiplegia After Traumatic Brain Injury

Abstract: A 51-year-old man showed hemiplegia on his right side after a traumatic brain injury (TBI). On initial brain computed tomography (CT) scan, an acute subdural hemorrhage in the right cerebral convexity and severe degrees of midline shifting and subfalcine herniation to the left side were evident. On follow-up brain magnetic resonance imaging (MRI), there were multiple microhemorrhages in the left parietal and occipital subcortical regions. To explain the occurrence of right hemiplegia after brain damage which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Neural injury in white matter is responsible for neurological disorders following traumatic brain injury (TBI) [1,2]. Many previous studies reported injury of the corticospinal tract (CST), which plays an important role in motor control, as is common in patients with TBI [1][2][3][4]. The prevalence of motor weakness after head injury was reported to range from 9% to 56% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Neural injury in white matter is responsible for neurological disorders following traumatic brain injury (TBI) [1,2]. Many previous studies reported injury of the corticospinal tract (CST), which plays an important role in motor control, as is common in patients with TBI [1][2][3][4]. The prevalence of motor weakness after head injury was reported to range from 9% to 56% [5].…”
Section: Introductionmentioning
confidence: 99%